Us vs. them the failure of globalism - Bremmer, Ian. (New York Portfolio, 2018)
Those who championed globalization once promised a world of winners, one in which free trade would lift all the world's boats, and extremes of left and right would give way to universally embraced liberal values. The past few years have shattered this fantasy, as those who've paid the price for globalism's gains have turned to populist and nationalist politicians to express fury at the political, media, and corporate elites they blame for their losses.
Includes bibliographical references (pages 170-190) and index.
Keywords: Anti-globalization movement